On the impact of the COVID-19 pandemic on the household’s consumption and labor supply: theory and application - Liu, Lu; Zhang, Yangyi (Technological and Economic Development of Economy, 2025)
The COVID-19 pandemic and the corresponding regulation measures carried out to curb it have had a strong negative impact on the whole economy, and household consumption has been seriously affected. A large part of the drop in consumption is due to the reduction of household income, which is mainly caused by the labor supply loss during the pandemic. To present the mechanism of the impact of the pandemic on consumption, this study constructs a novel theoretical model. Two hypotheses about the pandemic’s impact on labor supply are proposed and empirically tested. Subsequently, a comparative static analysis is carried out to determine the numerical mechanism of the pandemic’s impact on household consumption. In addition, the model is also empirically tested and further modified for application, enabling the studies of both a realistic simulation and a policy simulation. This study finds that the labor supply of households has been affected during the pandemic, and there is a mediating effect channel through the regulation stringency. The epidemic severity and regulation policies have a negative impact on household consumption, in turn, will raise the saving rate of households. The income effect of the two on consumption accounts for 32% and 44% of the total effect respectively. First published online 05 September 2024